PENINGKATAN KOSA KATA ANAK USIA DINI MELALUI LAGU REJANG DI TAMAN KANAK-KANAK BUNGA MEKAR DESA TUNGGANG KECAMATAN LEBONG UTARA KABUPATEN LEBONG PROVINSI BENGKULU - Rihana; Vivi Anggraini (STKIP Subang, 2026)
This study aimed to improve Rejang vocabulary mastery among early childhood learners through the use of Rejang folk songs at TK Bunga Mekar, Tunggang Village, North Lebong District, Lebong Regency, Bengkulu Province. The study was motivated by children's low mastery of Rejang vocabulary due to the dominance of Indonesian in daily communication, causing the local language to be used less frequently. The research employed Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 20 early childhood students. Data were collected through observation, documentation, and assessment of children's vocabulary mastery. The findings indicated that the use of Rejang folk songs significantly improved children's Rejang vocabulary mastery. In the pre-cycle stage, only 25% of children achieved the categories of Developing as Expected and Very Well Developed. After the implementation of the first cycle, the percentage increased to 55%, and further improved to 90% in the second cycle. The improvement was reflected in children's ability to recognize, understand, pronounce, and use Rejang vocabulary in simple communication. Therefore, Rejang folk songs are effective learning media for improving early childhood vocabulary mastery while supporting the preservation of local language and culture.